Dynamic changes of immunocyte subpopulations in thermogenic activation of adipose tissues - Ye, Yuqing; Wang, Huiying; Chen, Wei; Chen, Zhinan; Wu, Dan; Zhang, Feng; Hu, Fang (Frontiers in Immunology, 2024)
The effects of cold exposure on whole-body metabolism in humans have gained increasing attention. Brown or beige adipose tissues are crucial in cold-induced thermogenesis to dissipate energy and thus have the potential to combat metabolic disorders. Despite the immune regulation of thermogenic adipose tissues, the overall changes in vital immune cells during distinct cold periods remain elusive. This study aimed to discuss the overall changes in immune cells under different cold exposure periods and to screen several potential immune cell subpopulations on thermogenic regulation.Methods: Cibersort and mMCP-counter algorithms were employed to analyze immune infiltration in two (brown and beige) thermogenic adipose tissues under distinct cold periods. Changes in some crucial immune cell populations were validated by reanalyzing the single-cell sequencing dataset (GSE207706). Flow cytometry, immunofluorescence, and quantitative real-time PCR assays were performed to detect the proportion or expression changes in mouse immune cells of thermogenic adipose tissues under cold challenge.The proportion of monocytes, naïve, and memory T cells increased, while the proportion of NK cells decreased under cold exposure in brown adipose tissues.Our study revealed dynamic changes in immune cell profiles in thermogenic adipose tissues and identified several novel immune cell subpopulations, which may contribute to thermogenic activation of adipose tissues under cold exposure.